The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1590/s0102-76382001000400007
|View full text |Cite
|
Sign up to set email alerts
|

Profilaxia da fibrilação atrial no pós-operatório imediato de cirurgia coronária: comparação entre propranolol e sotalol utilizados em baixas doses

Abstract: C A, Cavalcanti I L -Profilaxia da fibrilação atrial no pós-operatório imediato de cirurgia coronária: comparação entre propranolol e sotalol utilizados em baixas doses. RESUMO: Objetivo: Comparar a eficácia de dois protocolos terapêuticos usando baixas doses de betabloqueadores para prevenção de fibrilação atrial no pós-operatório imediato de cirurgia coronária.Métodos: 154 pacientes, submetidos à cirurgia coronária, foram randomizados em dois grupos: no grupo I (n = 72), os doentes receberam Sotalol (80 mg/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…A randomized study of 253 patients showed a reduction in the incidence of AF with both drugs (sotalol being more effective) however the pro-arrhythmogenic effect of these drugs remains uncertain [13]. In another study, Wanderley et al [14], comparing the use of low-dose propranolol and sotalol in the postoperative period of CABG and obtained an overall incidence of AF of 7.1% which was lower in the group taking sotalol but without significant statistical difference. Ventral cardiac denervation, described by Arnulff in 1936, was widely employed in the prevention of coronary artery spasms in the 1970s.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized study of 253 patients showed a reduction in the incidence of AF with both drugs (sotalol being more effective) however the pro-arrhythmogenic effect of these drugs remains uncertain [13]. In another study, Wanderley et al [14], comparing the use of low-dose propranolol and sotalol in the postoperative period of CABG and obtained an overall incidence of AF of 7.1% which was lower in the group taking sotalol but without significant statistical difference. Ventral cardiac denervation, described by Arnulff in 1936, was widely employed in the prevention of coronary artery spasms in the 1970s.…”
Section: Discussionmentioning
confidence: 99%